Indahnya Mengampuni: Implementasi Nilai Kristen Di SD Negeri 176493 Parbubu Pea,Tarutung: Indahnya Mengampuni: Implementasi Nilai Kristen Di SD Negeri 176493 Parbubu Pea,Tarutung - Hutagalung, Eka; Damayanti Nababan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Forgiveness is one of the most fundamental basic values ​​in Christian teachings. This concept of forgiveness is so central because it reflects God's infinite love and His call for His people to live in unity and peace. SD Negeri 176493 Parbubu Pea emphasized the importance of a deep understanding of Christian values, especially for the younger generation. This article discusses Community Service (PKM) activities which aim to strengthen the faith of students at SD Negeri 176493 Parbubu Pea through understanding the beauty of forgiveness. The methods used in PKM include lectures, discussions, and games, which are designed to improve students' theological understanding and social skills. The results of the activities showed significant improvements in theological understanding, cooperation, and communication among students. This activity succeeded in achieving its goal, strengthening Christian values ​​and motivating students to spread the good news about the beauty of forgiveness and forgiveness.